ANALISIS STAKEHOLDERS DALAM PENATAAN PEDAGANG KAKI LIMA (PKL) KRIDANGGO KOTA - Yovi Hayuning Nitria; R. Slamet Santoso; Retna Hanani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Problems regarding street vendors are still often found in big cities, one of which is Salatiga. One of the Salatiga street vendors who experienced problems was Kridanggo street vendors who experienced a decrease in income after the arrangement. This study aims to determine the stakeholders who play a role in the arrangement of street vendors in Kridanggo and analyze the role each stakeholder has. This research method uses descriptive qualitative, with data collection through interviews, observation, documentation, and literature study. The interview technique was carried out to several informants, namely the Salatiga City Trade Office, Salatiga City Satpol PP, Head of the Kridanggo PKL Association, and Kridanggo PKL. The results of this study indicate that the role of the Salatiga City Trade Office is as a policy creator, coordinator, facilitator, implementor, and accelerator. The role of the Satpol PP is as the implementer or enforcer of regional regulations. The Paguyuban acts as a coordinator to the Trade Office and street vendors, facilitators, and accelerators by approaching street vendors. Meanwhile, PKL Kridanggo acts as an accelerator by facilitating the arrangement process